PENGARUH DISIPLIN DAN MOTIVASI DAN KINERJA PEGAWAI DINAS PETERNAKAN DAN KESEHATAN HEWAN PROVINSI BENGKULU - Tito Irwanto; Tri Febrina Melinda (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
Tito Irwanto, Tri Febrina Melinda; The purpose of this study was to determine the effect of discipline and motivation to employee performance Department of Animal Husbandry and Animal Health Bengkulu Province. This type of research used in this research is quantitative. The collection of data by distributing questionnaires to employees of the Department of Animal Husbandry and Health Bengkulu province amounted to 100 employees using simple random sampling. The analysis method used by Multiple Regression Analysis, Correlation Analysis, T Test, F Test and Test The coefficient of determination (R2). The analysis showed that the discipline and motivation positive influence on employee performance.Key Word: Dicipline, Motivation and Performance